2008
DOI: 10.1143/apex.1.041101
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Dependence of Nonpolarm-Plane InxGa1-xN/GaN Light Emitting Diodes

Abstract: Characteristics of m-plane InGaN/GaN light emitting diodes (LEDs) with various indium compositions were investigated. X-ray diffraction revealed that indium compositions in the InGaN multi quantum wells (MQWs) on m-plane substrate were 2 -3 times lower than those on c-plane substrate. The optical polarization ratio for m-plane LEDs increased from 0.27 to 0.89 with increasing emission wavelength from 383 to 476 nm due to compressively strained InGaN QWs. The output power of electroluminescence decreased above 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 24 publications
6
50
1
Order By: Relevance
“…The polarization ratio r is defined as r ¼ (I a -I c )/(I a +I c ), where I a and I c denote EL intensity at 1 mA with polarization parallel to the a-and c-axis, respectively. The polarization ratio of the on-axis m-plane LED increased from 0.27 to 0.89 with increasing emission wavelength from 383 to 476 nm, corresponding to the indium composition from 0.02 to 0.08 [16]. The dependence of the polarization ratio on emission wavelength is explained by the energy separation in the valence band, which is caused by the compressively strained InGaN QWs [21,22].…”
Section: Article In Pressmentioning
confidence: 92%
See 1 more Smart Citation
“…The polarization ratio r is defined as r ¼ (I a -I c )/(I a +I c ), where I a and I c denote EL intensity at 1 mA with polarization parallel to the a-and c-axis, respectively. The polarization ratio of the on-axis m-plane LED increased from 0.27 to 0.89 with increasing emission wavelength from 383 to 476 nm, corresponding to the indium composition from 0.02 to 0.08 [16]. The dependence of the polarization ratio on emission wavelength is explained by the energy separation in the valence band, which is caused by the compressively strained InGaN QWs [21,22].…”
Section: Article In Pressmentioning
confidence: 92%
“…However, the emission wavelength of the on-axis m-plane LEDs was shorter than that of the c-plane LEDs. This is because the indium incorporation in the on-axis m-plane InGaN/GaN quantum wells (QWs) is shorter than that in the c-plane QWs [16]. In this study, we investigated effects of off-axis substrates on the m-plane InGaN/GaN LEDs and have found that the off-axis substrates toward the c À -direction (N-polar) significantly affect the ratio of the indium composition in the InGaN/GaN QWs.…”
Section: Introductionmentioning
confidence: 99%
“…5.9 Schematic of the principle polar, non-polar and semi-polar planes of GaN. The QCSE effect should be eliminated by growing along a non-polar direction such as and [11][12][13][14][15][16][17][18][19][20] or minimised along a semi-polar direction such as [11][12][13][14][15][16][17][18][19][20][21][22] times lower than along the c-plane for similar growth conditions [37]. The output power of the non-polar LEDs also reduced dramatically when the emission wavelength was longer than 400 nm.…”
Section: Internal Electric Fieldmentioning
confidence: 99%
“…Theoretical studies suggested that the undesired internal fields can be avoided by fabricating devices on nonpolar surface perpendicular to c-plane, i.e., m-plane {1 1 0 0} or a-plane {1 1 2 0} [4]. In the last few years, the growth of III-nitrides in nonpolar direction, so-called nonpolar nitrides, has drawn considerable research interest due to its potential to improve the light efficiencies of optoelectronic devices [6][7][8][9][10][11][12]. All the theoretical and experimental reports showed that growth and device design with active regions parallel to the nonpolar crystallographic planes is a promising approach to achieve enhanced emission, especially in the green region, which has been problematic for a long time [13].…”
Section: Introductionmentioning
confidence: 99%